Guide to hedge funds : what they are, what they do, their risks, their advantages - Coggan, Philip (London: The Economist in association with Profile Books, 2011)
In 1990 hedge funds managed some $39 billion of assets. By late 2006 that figure had grown to $1.3 trillion. Most people have heard of the term 'hedge funds' but few are clear about what exactly a hedge fund is or what it does. This guide provides a survey of the industry for all those who think they should know about hedge funds, but do not.
Includes index.
Keywords: Finance and accounting